A positive feedback loop between RIP3 and JNK controls non‐alcoholic steatohepatitis. Issue 8 (24th June 2014) - Gautheron, Jérémie; Vucur, Mihael; Reisinger, Florian; Cardenas, David Vargas; Roderburg, Christoph; Koppe, Christiane; Kreggenwinkel, Karina; Schneider, Anne Theres; Bartneck, Matthias; Neumann, Ulf Peter; Canbay, Ali; Reeves, Helen Louise; et al.
Abstract: Non‐alcoholic fatty liver disease (NAFLD) represents the most common liver disease in Western countries and often progresses to non‐alcoholic steatohepatitis (NASH) leading ultimately to liver fibrosis and liver cancer. The occurrence of hepatocyte cell death—so far characterized as hepatocyte apoptosis—represents a fundamental step from benign steatosis toward progressive steatohepatitis. In contrast, the function of RIP3‐dependent "necroptosis" in NASH and NASH‐induced fibrosis is currently unknown. We show that RIP3 is upregulated in human NASH and in a dietary mouse model of steatohepatitis. RIP3 mediates liver injury, inflammation, induction of hepatic progenitor cells/activated cholangiocytes, and liver fibrosis through a pathway suppressed by Caspase‐8. This function of RIP3 is mediated by a positive feedback loop involving activation of Jun‐(N)‐terminal Kinase (JNK). Furthermore, RIP3‐dependent JNK activation promotes the release of pro‐inflammatory mediators like MCP‐1, thereby attracting macrophages to the injured liver and further augmenting RIP3‐dependent signaling, cell death, and liver fibrosis. Thus, RIP3‐dependent necroptosis controls NASH‐induced liver fibrosis. This pathway might represent a novel and specific target for pharmacological strategies in patients with NASH. Synopsis: RIP3‐dependent necroptosis mediates NASH‐induced liver fibrosis via activation of JNK, MCP‐1‐mediated recruitment of monocytes, and an expansion of intrahepatic biliary/progenitor cells. Caspase‐8 appears to suppress the deleterious effect of RIP3. RIP3 mediates liver injury in MCD‐diet‐induced NASH. RIP3—similar to Caspase‐8—does not affect CCl4‐induced liver fibrosis and thus might be a specific target in metabolic liver disease. Human NASH livers strongly express RIP3. Targeting RIP3 might represent a novel‐specific approach in human NASH. Abstract : RIP3‐dependent necroptosis mediates NASH‐induced liver fibrosis via activation of JNK, MCP‐1‐mediated recruitment of monocytes, and an expansion of intrahepatic biliary/progenitor cells. Caspase‐8 appears to suppress the deleterious effect of RIP3.